HAKIKAT, SUMBER, DAN KLASIFIKASI PENGETAHUAN DALAM PERSPEKTIF FILSAFAT DAN ISLAM - Zuhria, Fristika Maulida Aminatuz; Barqul Fuadi, Mohammad Nuril; Firdzan Zazuli, Muhammad Alif (Universitas Nahdlatul Ulama Surakarta, 2025)
This study aims to examine the nature, sources, and classification of knowledge from the perspectives of Western philosophy and Islamic thought. Using a descriptive qualitative approach through the method of library research, data were collected from relevant primary and secondary literature. The analysis was conducted using historical and thematic approaches by examining philosophical texts as well as classical and contemporary Islamic literature. The findings show that Western philosophy classifies knowledge based on its origins namely empirical (based on experience), rational (based on reason), and intuitive (based on intuition) and distinguishes between a priori knowledge (prior to experience) and a posteriori knowledge (derived from experience). Meanwhile, Islamic epistemology regards revelation, reason, and the senses as complementary sources of knowledge that do not contradict one another. Knowledge in Islam is also classified hierarchically, such as ‘ilm al-yaqīn (knowledge through reliable information), ‘ayn al-yaqīn (knowledge through direct observation), and haqq al-yaqīn (true and certain knowledge). Furthermore, knowledge in Islam is differentiated into naqliyah and aqliyah sciences, fardhu ‘ain and fardhu kifayah obligations, as well as worldly and otherworldly knowledge. Comparatively, Western epistemology tends to be secular and separates the spiritual dimension from the sources of knowledge, whereas Islam integrates the divine dimension throughout the entire epistemic process. Thus, the Islamic paradigm of knowledge is holistic and transcendental, in contrast to the Western approach, which tends to be dualistic and fragmentary. These findings highlight that in Islam, knowledge is not only a means of understanding reality but also a path toward closeness to God and the construction of a meaningful life. This study emphasizes the importance of an integrative approach in understanding and developing knowledge, particularly in addressing the entrenched dichotomy of sciences in contemporary education. In this context, Islamic thought and Western philosophy can, in fact, enrich one another. Although Western epistemology tends to emphasize the rational and empirical aspects while detaching them from the spiritual dimension, the systematic and analytical methods developed in Western traditions can complement the Islamic worldview, which is both transcendental and ethical. By critically and selectively linking the two, it becomes possible to construct a more holistic framework of knowledge one that is not only focused on technical advancement but also spiritually and ethically meaningful for humanity.